A NEW METHOD FOR ANALYZING ELECTRON MICROSCOPE AUTORADIOGRAPHS USING HYPOTHETICAL GRAIN DISTRIBUTIONS - Blackett, N. M. (The Rockefeller University Press, 1973)
A new method for the analysis of electron microscope autoradiographs is described which has two advantages over other methods. This method provides estimates for the activity in different regions of the section and takes into account the actual geometrical shape and position of different regions within the section. Use is made of the measured distribution of grains about a thin line source to construct a hypothetical distribution of autoradiographic grains which is then compared with the actual distribution of grains. Different activities are then ascribed to various regions until a satisfactory agreement with the autoradiographic grains is obtained using the χ(2) significance. In the next paper, an example of the use of this method is given for the distribution of grains in the nucleus of erythroid bone marrow cells labeled with radioactive iron, (55)Fe.